Ensino superior em Turismo: uma análise da relação dos cursos acadêmicos de Turismo da cidade do Natal-RN e o mercado de trabalho na percepção dos egressos dos anos de 2009 e 2010 - Pequeno, Edilene Adelino (2012)
The process of development of any area is closely linked to teaching and research, and in Tourism it is not different. Thus, in this area in which service is one of the factors intrinsically related to its success , it is observed the need for people with deep and critical training in the various aspects of this activity acting in this sector. However, we can see the existence of some differences between what is offered by the academy from what is required by the market. Therefore, the objective of this research is to verify the relationship between higher education in Tourism and labor market through the perception of the bachelor in this area, graduated in Natal-RN, since it is the tourismologist who makes the link between this two fields. To know the perception of these tourismologists, it was necessary to apply a questionnaire to those ones graduated in the years 2009 and 2010. In accordance with the aim of this study, this research was exploratory-descriptive. Related to the technical procedures, it was a documentary, literature and field research. To have it analyzed, some qualitative and quantitative techniques were applied according to our specific objectives and the types of data collected, such as: content analysis, factorial analysis to synthesize the information and identify the basic dimensions that represent the different variables studied, the standard deviation to verify the variation of the responses in some items and the correlation technique that allows the analysis of the relationship between two variables. In response to the objectives proposed here, we could finally conclude that: the syllabuses of these courses are too general and the graduates themselves consider them so. It was diagnosed that the graduates 1) are mostly female, 2) a very small part of them is working in the area that they are graduated in, and 3) not all of them receive satisfactory wages which contributes to having a negative view of their degree course. Moreover, the educational institution where they studied was not a decisive factor to get a job. It was still diagnosed that most part of them do not have positive perceptions when thinking about the future of their careers as bachelors in Tourism. Many of them, including, if it was possible to change something in their careers so far, they could have chosen another college degree. It was found that, although there is a negative perception about their professional future, almost half of them believe that the course met the needs of the market. However, those ones that are not working have a more positive point of view related to the applicability of higher education. On the other hand, the other ones who already worked in this area have a more negative perception about it and do not believe that the course meets the market's needs. In summary, this study allowed the understanding of the existence of some gaps that exist between higher education in Tourism and the market needs, professionally speaking, thus contributing to the spreading of ideas on that subject for teachers, researchers and the current and future students of the area.